Heat Transfer in Circulating Fluidized Beds - Wirth, Karl-Ernst (Chemical Engineering Science, 1995)
The wall-to-suspension heat transfer in circulating fluidized beds depends on the fluid mechanics immediately near the wall and on the thermal properties of the gas used. Experimental investigations of circulating fluidized beds of low dimensionless pressure gradients with different solid particles like bronze, glass and polystyrene at ambient temperatures show no influence of the conductivity and the heat capacity of the solids on the heat transfer coefficient. Consequently the heat transfer coefficient in form of the dimensionless Nusselt number can be described in dependence of dimensionless numbers which characterize the gas-solid flow near the wall. These numbers are the Archimedes number and the pressure-drop number. The last number relates the cross-sectional average solids concentration to the solids concentration at minimum fluidization condition. With the aid of the model of the segregated vertical gas-solid flow the flow pattern in the wall region can be calculated and consequently the wall heat transfer which depends only on heat conduction in the gas and on the convective heat transfer by the gas. With elevated suspension temperatures radiation contributes additionally to the heat transfer. When the solids concentration is low the effect of the radiation on the heat transfer is high. Increasing solids concentration results in a decrease of the radiation. With high solids concentration the wall will be shielded by the cold solids clusters moving down the wall from the radiation of the hot particles in the core region. A simple correlation is presented for calculating the heat transfer in circulating fluidized beds. © 1995.
UnivIS-Import:2015-03-05:Pub.1995.tech.ITC.mechve.heattr_36